PENGARUH KEPRIBADIAN DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SEKOLAH MENGAH ATAS NEGERI DI KECAMATAN BEKASI UTARA, BEKASI - Imanda Priskila Sinamo (Jurnal Manajemen Pendidikan, 2016)
The purpose of this research is to determine the effect of personality and job satisfaction on organizational citizenship behavior the teacher sma the district of noth bekasi. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) personality has a positive direct effect in organizational citizenship behavior, (2) job satisfaction has a positive direct effect in organizational citizenship behavior, (3) personality has a positive direct effect in job satisfaction